Testes funcionais aplicados sob supervisão direta (face-to-face) e indireta (telemonitoramento) em crianças e adolescentes com Fibrose Cística: um estudo de viabilidade - Calasans, Georgia Aparecida Santos de Araújo (2021)
In times of the COVID-19 pandemic, it would be useful to assess the functional capacity of fibrocystics children and adolescents in their own homes by clinical field tests.Objective: To evaluate the feasibility and safety of conducting functional capacity tests by telemonitoring in fibrocystics children and adolescents. Methods: Fibrocystic children and adolescents underwent: 3-minute step test (TD3), 1-minute sit-to-stand test (TSL-1min) and timed up and go test (TUG) in two randomized visits, both at the patient's home, supervised directly (face-to-face) and indirectly (telemonitoring). The number of steps in the TD3, the number of repetitions in the TSL-1min, the time taken to perform the TUG and its physiological variables were compared between supervisions. The feasibility assessment included: interaction with the evaluator, quality of sound and video instruction, experience of the participant, best method according to the participant and safety of the method. Results: 32 children and adolescents were recruited (15 boys, 11 ± 3 years, FEV1 73 ± 17% of predicted). The performances between face-to-face and telemonitoring were similar in TD3 [88 (79-90) and 88 (63-90) number of steps, respectively], in TSL-1min [35 (19-51) and 33 (17- 55) repetitions, respectively] and TUG [6 (4-11) and 6 (4-12) seconds, respectively]. Participants reported good interaction with the evaluator [5 (3-5)], video and sound quality [5 (3-5) and 4 (1-5)], respectively) and experience [5 (3-5)]. Safety was classified as low risk for 56% of the sample. Conclusion: The TD3, TSL-1min and TUG tests were feasible and safe to be performed by telemonitoring.